Artevelde : de mythe en de man - De Mont, Paul (Brussel : Elsevier, 1948)
Bibliotheek Camille Huysmans
Dedicator: De Mont, Paul, dedicatee: Huysmans, Camille
Nederlands
Monografie
Keywords: Van Artevelde, Jacob